PENGGUNAAN AUTHENTIC MATERIAL UNTUK PERGURUAN TINGGI VOKASI - Ayuningtyas, Pratika (Penerbit Widina, Widina Media Utama, 2023)
Vocational education has a primary goal, namely to produce students who are ready to work in the real world. With a fundamental difference, namely prioritizing practice in learning, the materials obtained by students are expected to be able to provide knowledge equivalent to real work experience. One of the courses that prioritizes soft skills in vocational education is English for Specific Purposes (ESP). In ESP courses, the use of Authentic Material can provide a bridge for students to gain access to the real world in the classroom. One of the study programs at Sawunggalih Aji Polytechnic that applies the use of authentic materials in its courses is the Accounting Study Program. The use of Authentic Material provides real life knowledge for Accounting students in creating business letters and in creating examples of video advertisements. So, by applying authentic materials in the classroom, students will get to know the real world better even though they are only studying in the classroom.ABSTRAKPendidikan vokasi memiliki tujuan primer yaitu untuk mencetak peserta didik yang siap kerja di dunia nyata. Dengan perbedaan yang mendasar yaitu mengedepankan praktek dalam pembelajarannya, materi-materi yang didapatkan peserta didik diharapkan mampu memberikan pengetahuan yang setara dengan pengalaman kerja nyata. Salah satu mata kuliah yang mengedepankan softskills pada pendidikan vokasi adalah English for Specific Purposes (ESP). Pada mata kuliah ESP, penggunaan Authentic Material dapat menjembatani peserta didik untuk mendapatkan akses kepada dunia nyata di dalam kelas. Salah satu program studi di Politeknik Sawunggalih Aji yang menerapkan penggunaan authentic material dalam mata kuliahnya adalah Prodi Akuntansi. Penggunaan Authentic Material memberikan pengetahuan real life untuk mahasiswa Akuntansi dalam membuat surat bisnis maupun dalam membuat contoh iklan video. Maka, dengan mengaplikasikan authentic material di dalam kelas, mahasiswa lebih mengenal dunia nyata meskipun hanya belajar di dalam kelas.